MBG (Makan Bergizi Gratis) sebagai Instrumen Pemberdayaan Ekonomi Lokal: Analisis Model SPPG dan Tantangan Tata Kelola Publik - Saepuloh Saepuloh; Fuad Hilmi (EKALAYA : Jurnal Ekonomi Akuntansi, 2026)
This article examines the Free Nutritious Meal Program (MBG) as a hybrid public policy instrument that integrates social nutrition intervention with local economic empowerment. The study focuses on analyzing the role and operational mechanism of the Nutrition Service Unit (SPPG) in stimulating local economic ecosystems, identifying governance challenges emerging in its implementation, and formulating strategies to strengthen oversight systems to ensure sustainability and accountability. Employing a qualitative descriptive approach through policy analysis, this research analyzes official policy documents, including the Decree of the Head of the National Nutrition Agency No. 244 of 2025, supported by relevant literature on Local Economic Development and Good Governance. The findings indicate that SPPG functions not only as a food distribution mechanism but also as a fiscal stimulus capable of generating local multiplier effects through partnerships with farmers, livestock producers, and food MSMEs. However, governance challenges such as limited digital monitoring integration, potential conflicts of interest, and performance-based audit constraints may weaken program effectiveness. The study proposes an integrated economic–oversight model to enhance transparency, accountability, and long-term structural impact.